Organizational predictors of workplace deviance among support staff - Alias, Mazni; Mohd Rasdi, Roziah (Elsevier, 2015)
The study seeks to examine the influences of organizational-related factors among 220 support staff in a Malaysian government organization. Specifically, it seeks to determine the influence of perceived organizational support, organizational justice, organizational ethical climate, and trust in organization on interpersonal and organizational deviance. This study employed cross-sectional survey involving a sample of 220 support staff. The findings highlighted that perceived organizational support and organizational ethical climate influences interpersonal deviance whereby organizational justice and perceived organizational support influences organizational deviance among the support staff. This study suggests human resource professionals to use their expertise in reducing workplace deviance.